Anti-microbial coating innovations to prevent infectious diseases (AMiCI): Cost action ca15114. Issue 6 (2nd November 2017) - Dunne, Colum P.; Keinänen-Toivola, Minna M.; Kahru, Anne; Teunissen, Birgit; Olmez, Hulya; Gouveia, Isabel; Melo, Luis; Murzyn, Kazimierz; Modic, Martina; Ahonen, Merja; Askew, Pete; Papadopoulos, Theofilos; et al.
ABSTRACT: Worldwide, millions of patients are affected annually by healthcare-associated infection (HCAI), impacting up to 80, 000 patients in European Hospitals on any given day. This represents not only public health risk, but also an economic burden. Complementing routine hand hygiene practices, cleaning and disinfection, antimicrobial coatings hold promise based, in essence, on the application of materials and chemicals with persistent bactericidal or –static properties onto surfaces or in textiles used in healthcare environments. The focus of considerable commercial investment and academic research energies, such antimicrobial coating-based approaches are widely believed to have potential in reduction of microbial numbers on surfaces in clinical settings. This belief exists despite definitive evidence as to their efficacy and is based somewhat on positive studies involving, for example, copper, silver or gold ions, titanium or organosilane, albeit under laboratory conditions. The literature describes successful delay and/or prevention of recontamination following conventional cleaning and disinfection by problematic microbes such as methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin resistant enterococci (VRE), among others. However, there is a scarcity of studies assessing antimicrobial surfaces other than copper in the clinical environment, and a complete lack of published data regarding the successful implementation of these materials on clinically significant outcomes (including HCAI). Through its Cooperation in Science and Technology program (COST), the European Commission has funded a 4-year initiative to establish a network of stakeholders involved in development, regulation and use of novel anti-microbial coatings for prevention of HCAI. The network (AMiCI) comprises participants of more than 60 universities, research institutes and companies across 29 European countries and, to-date, represents the most comprehensive consortium targeting use of these emergent technologies in healthcare settings. More specifically, the network will prioritise coordinated research on the effects (both positive and negative) of antimicrobial coatings in healthcare sectors; know-how regarding availability and mechanisms of action of (nano)-coatings; possible adverse effects of such materials (e.g., potential emergence of microbial resistance or emission of toxic agents into the environment); standardised performance assessments for antimicrobial coatings; identification and dissemination of best practices by hospitals, other clinical facilities, regulators and manufacturers.